Bilateral Yokoyama procedure in a patient with esotropic strabismus fixus due to severe myopia - Pelińska, Katarzyna; Peredysta, Valeriia; Sildatke-Bauer, Magdalena; Loba, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
The aim of this case report is to present successful management of bilateral esotropic strabismus fixus due to severe myopia in a 63-year-old female patient. Myopic strabismus fixus is a rare condition that develops in patients with high myopia due to enlarged dimensions of the globe. This type of ocular misalignment may progress from small angle esotropia with free ocular movements, to the stage in which one or both eyes are anchored in a position of extreme adduction. In the case presented, esotropia was so severe that both eyes were fixed in an adducted position. The patient had to adopt a severe head turn in order to make use of her better eye; nevertheless her visual function was poor. We performed a bilateral Yokoyama procedure with simultaneous medial rectus recession. The surgery resulted in a large improvement of ductions and reduction of esotropia. The patient’s visual function improved substantially and the head turn was vastly reduced.